The Effectiveness of Pull Up Exercises to Improve Throw-In Ability in Football - La Ode Muammar Kadas Hidayat; Marsuna (S&Co Publishing, 2026)
This study aims to determine the effectiveness of pull-up training on throw-in ability in football games. This type of research is an experimental study with a one-group pre-test post-test design. The population is the entire target of the study, namely 267 students of SMA Negeri 05 Bombana. With 144 females and 123 male students who are active in school. Sampling in this study used a purposive sampling technique. This method was carried out based on certain considerations. With the criteria of male gender and being able to do a throw-in, so that in this study there were 30 people. The research instrument used was a throw-in ability test. Based on the results of the analysis using the t-test, it was obtained that pull-up training had a significant effect on throw-in ability, with a t-count value of 7.51 greater than the t-table of 2.042 at a significance level of 0.000 <0.05. In addition, there was an increase in throw-in ability of 2.94% from pre-test to post-test after being given pull-up training. Thus, pull-up training is proven to be effective in improving throw-in ability in football.